THEORETICAL AND PRACTICAL ASPECTS OF SERVICEMEN PSYCHOLOGICAL REHABILITATION UNDER CONDITIONS OF COMBAT SITUATION AND AFTER THE ENGAGEMENT - Алещенко, В. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
Psychological rehabilitation is analyzed as an integral part of social, medical and psychological rehabilitation. The author has considered its basic stages, the principles of conduct, a set of measures, which is organized by commanders, deputies for work with personnel, psychologists in order to restore mental and physical resources personnel as a result of receiving the combat stress on the battlefield. The experience of psychological rehabilitation application in a combat situation is analyzed. The main theoretical conclusions and practical recommendations to ways her improving in the combat situation conditions and after the battle have been formalized. Key words: The Armed Forces of Ukraine, a serviceman, a stress- factor, psychological help, psychological rehabilitation.